Philanthropy in Pesantren: A Review - Uula, Mimma Maripatul; Ali, M. Mahbubi (The Economic Review of Pesantren, 2025)
This study aims to map the development and direction of research on Islamic Boarding Schools & Philanthropy through a bibliometric approach. The research data is sourced from scientific journal publications indexed in the Dimensions database with the keyword "Pesantren & Philanthropy". A total of 27 relevant articles were analyzed using the VOSviewer software to identify the co-occurrence patterns of keywords, research clusters, and trends of developing research themes. The results of the analysis show that research on pesantren philanthropy is concentrated in three main clusters, namely: (1) pesantren philanthropy management, (2) human capital development in pesantren studies, and (3) pesantren based economic empowerment strategies. These findings indicate that Islamic philanthropy in Islamic boarding schools not only functions as a social assistance mechanism, but also as a strategic instrument in institutional strengthening, human resource development, and economic independence. This study makes a conceptual contribution by presenting a comprehensive research map and opening up opportunities for further research related to the integration of Islamic boarding school philanthropy with the sustainable development agenda.